Identifying and Prioritizing of Factors Affecting the Acceptance of Electronic Services from the Perspective of Citizens - Fatemeh MalekiTabas; Nour Mohammad Yaghoubi; Mehri Rajaei (International Journal of Business and Development Studies, 2021)
This study was carried out aimed to identify and prioritize the factors affecting the acceptance of electronic services from the perspective of the Iranian citizens. The present study is considered as an applied-developmental research in terms of purpose and qualitative and quantitative research in terms of method. Library studies, interviews, and questionnaires were used to collect data. The questionnaire had face validity and Cronbach's alpha and composite reliability were used to estimate its reliability. The statistical population related to the qualitative study, included professors in the field of e-government and active executive experts working in the Ministry of Communications and Information Technology, the Administrative and Employment Organization, and the Management and Planning Organization are 17 people who were selected using targeted snowball sampling. The statistical population related to the quantitative study, included the Iranian citizens, 384 people were selected from the infinite population according to Morgan's table and were examined according to the infinite statistical population. LISREL software, SPSS and one-sample t-test were used to analyze the data. According to the results, the factor of citizens 'efficiency, perceived usefulness, perceived ease have the greatest impact on the acceptance of electronic services from the citizens' point of view, respectively.